The role of stereotactic radiotherapy in the treatment of the local recurrence of colorectal cancer - a case report - Radosavljević, Kristina; Ivanov, Olivera; Bojović, Marko; Ličina, Jelena; Protić, Mlađan; Prvulović Bunović, Nataša (Archive of Oncology, 2024)
Colorectal cancer is one of the most common malignant diseases worldwide. A multidisciplinary approach to treatment involves surgery and chemotherapy, while radiotherapy is used in the treatment of tumors localized in the pelvis. Stereotactic radiotherapy allows the delivery of high, ablative radical radiotherapy doses to target volumes, with a reduced risk to the surrounding organs, making it suitable for irradiating localized disease. A 59-year-old female S.M. presented to the doctor due to the appearance of a perianal fistula. Colonoscopy was performed, revealing a moderately differentiated adenocarcinoma. Magnetic resonance imaging (MRI) examination diagnosed a tumor lesion of the rectosigmoid junction with a perilesional abscess collection and several fistulous channels communicating with the perianal skin. The patient underwent surgery with adjuvant chemotherapy. A follow-up MRI examination 8 months after surgery revealed a soft tissue lesion in the perianal tissue characterized as a recurrence of the disease, and stereotactic body radiotherapy (SBRT) was applied. Six months after SBRT follow-up examinations indicated a complete clinical response to radiotherapy without the recurrence of the primary disease. Stereotactic radiotherapy can be applied as an effective and safe ablative technique, particularly when considering the significant morbidity and impairment of the quality of life in patients after surgical treatment.